Domestic animals of backyard in the forest deciduo of land lands of the Commune San Marcos parish Colonche - Cabrera Mayorga, Isabel (2019)
The work was carried out in the San Marcos commune, Colonche parish, the objective was to identify the social and current environment of the Creole domestic animals existing in the area of the deciduous lowland forest. The study used a previously structured survey, which investigated the family structure, socio-economic characteristics and management of animals. The results indicate that there is a direct participation of 50 % of men aged 45 years and older, where 65 % cannot read or write, families are made up of 66,66 % of 4-5 people; In the commune there is presence of hens, goats and Creole pigs. These animals develop freely in all areas of the commune. The results report that on average the inhabitants have nine hens, seven goats and four Creole pigs in different physiological stages; These animals are constantly in grazing. Their main food source is the products and by-products of crops with 50 %, 15 % of household waste and remain 100 % to grazing; the production obtained from meat, milk, eggs of these animals 30 % is for family consumption and 70 % for sale; the animals do not have infrastructure in the raising so 70 % of these have semi-extensive management. This indicates that Creole domestic animals have been an important part of the nutrition of families in the community of San Marcos and support for their family economy.